Comparison between tamoxifen and clomiphene citrate for induction of ovulation and successful conception in polycystic ovarian syndrome - Hassan, Zhyan Baker (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Being a selective estrogen receptor inhibitor (SERM) tamoxifen may be used an alternative to clomiphene citrate for ovulation induction in women with anovulatory infertility. This study was conducted to evaluate the safety and efficacy of tamoxifen as compared to clomiphene citrate in women with primary or secondary anovulatory infertility due to Polycystic Ovarian Syndrome (PCOS). Methods: One hundred women suffering from anovulatory infertility and attending the infertility clinic and were recruited for the study. Patients were randomized to receive either clomiphene citrate (100-150 mg) or tamoxifen treatment (40-80 mg). The ovulation was monitored from day 5 to day 9 of menstrual cycle followed up by transvaginal ultrasound from day 11 every alternate day for 10 days. Ovulation and pregnancy rates were calculated. Results: The baseline characteristics of mean age, weight, proportion of patients with primary and secondary infertility and mean duration of infertility were comparable between both the study groups. Out of 50 patients who received clomiphene citrate, 37 showed successful ovulation (ovulation rate of 64%) and 16 patients conceived (pregnancy rate of 32%). In tamoxifen group 41 women showed successful ovulation (ovulation rate of 82%) and 18 women conceived (pregnancy rate of 36%). The difference was not significantly different (p > 0.05). No major adverse effects were noted in both the study groups. Conclusions: Tamoxifen has shown comparable efficacy and safety as compared to clomiphene citrate and it can be a good alternative to clomiphene citrate in patients of primary or secondary anovulatory infertility with PCOS.